The Cumulative Approach in the System of Scientific Knowledge and Its Application to the Development of Regional Innovation System - Olga SMYSLOVA; Natalia IVANOVA; Anastasia KOKOREVA; Timofei BASHLYKOV; Natalia MOROZOVA (Communications of International Proceedings, 2021)
The paper addresses the issues of using a cumulative approach to the formation and development of the regional innovation system. The relevance of the topic is conditioned by the growing interest in regional systems, as part of the national innovation system, as well as the peculiarities of the spatial and economic development of regions. The number of cumulation concepts is examined in various scientific fields and the theories of cumulative growth are analyzed by the authors. The strengths of each theory are defined and an appropriate algorithm for applying a cumulative approach in the region is compiled. The study comprises methods of empirical research (comparison, collection and study of information), the current and perspective analysis and the synthesis of theoretical and practical materials. The materials of the study enable to systematize approaches to the management of regional innovation systems aimed at the most productive problem-solving methods creating which regional innovative activity inevitably entails and hinders its turn the regional development.
Keywords: Cumulative Approach; Cumulative Growth Theories; Special Economic Zones Of Regional Type; Regional Innovation System